Design strategy of a compact unglazed solar thermal facade (STF) for building integration based on BIM concept - Shen, Jingchun; Zhang, Xingxing; Yang, Tong; Tang, Llewellyn; Wu, Yupeng; Pan, Song; Wu, Jinshun; Xu, Peng (Elsevier, 2017)
This paper discusses the specific design strategy of a novel compact unglazed Solar Thermal Facade (STF) for building performance research in architectural practice. It identifies the basic role of such STF in the building performance simulation and analysis. A dedicated design strategy based on the BIM (building information modelling) concept for application of the proposed STF is then developed in details. This research work clarifies the necessary steps in ensuring that the environmental/economic factors and energy-efficiency strategies of the STF are integrated with the building design and analysis process at the early stage.